2004
DOI: 10.1111/j.1742-1241.2004.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

The medicinal use of cannabis in the UK: results of a nationwide survey

Abstract: The use of cannabis for medical purposes is a controversial but an important topic of public and scientific interest. We report on the results of a self-administered questionnaire study conducted in the United Kingdom between 1998 and 2002. The questionnaire consisted of 34 items and included demographic data, disease and medication use patterns and cannabis use profiles. Subjects were self-selected; 3663 questionnaires were distributed and 2969 were returned [1805 (60.9%) women, mean age 52.7 years (SD 12.7)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
159
5
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(189 citation statements)
references
References 16 publications
16
159
5
5
Order By: Relevance
“…Clinical studies have reported benefits of cannabis on mood disorders (Ashton et al, 2005;Ware et al, 2005). Genetic (Haller et al, 2002(Haller et al, , 2004Martin et al, 2002) or pharmacological (Navarro et al, 1997;Deroche-Gamonet et al, 2001) CB 1 R blockade in murine models yields enhanced expression of depression/ anxiety-like behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have reported benefits of cannabis on mood disorders (Ashton et al, 2005;Ware et al, 2005). Genetic (Haller et al, 2002(Haller et al, , 2004Martin et al, 2002) or pharmacological (Navarro et al, 1997;Deroche-Gamonet et al, 2001) CB 1 R blockade in murine models yields enhanced expression of depression/ anxiety-like behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In Canada, the Medical Marijuana Access Regulations provides a legal means for patients, with the support of their physician, to be authorized to use marijuana for medical purposes. Most of the people who use marijuana for medical purposes use it by the smoking route (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The primary components of the endocannabinoid signaling system (CB1, CB2, and FAAH) are characteristically expressed in the synovium of both osteoarthritic (OA) and rheumatoid arthritic (RA) patients, with compelling evidence to demonstrate an active participation in the pathophysiology of joint pain (35). Preclinical and clinical studies support the therapeutic application of cannabinoids in the treatment of chronic pain, and to date, patients suffering from chronic arthritic and musculoskeletal pain represent the most prevalent users of medicinal cannabis (36). Despite this optimism, hesitation in clinical application is prevalent with extensive guidelines published in different countries (37)(38)(39).…”
Section: Endocannabinoids and Arthritic Painmentioning
confidence: 99%
“…More recently, an increased expression of CB1 accompanied by OA development has been demonstrated (36). CB1 receptors are located on peripheral sympathetic nerve terminals as well as on nociceptive nerve fibers, where they modulate adrenergic signaling to influence cytokine production (44).…”
Section: Changes In Cb Receptor Expressionmentioning
confidence: 99%